The Impacts of BMT Empowerment Program to MSMes Development: A Case Study in Magelang - Fahmi Medias; Eko Kurniasih Pratiwi; Nasitotul Janah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
AbstractThis study aims to determine the impact of the BMT (Baitul Maal wa Tamwiil)empowerment program on the development of MSMEs (Micro, Small, andMedium Enterprises) in Magelang. From this research, it is hoped that it canprovide accurate data and maps about the extent to which programs andactivities that have been carried out by BMT influence MSMEs in MagelangRegency, with indicators: BMT and UMKM profiles; access that MSMEs haveto the BMT program, programs that have been implemented by BMT and theimpact of the BMT program on the development of MSMEs. This research usesdescriptive qualitative analysis. Respondents in this study consisted of severallarge BMTs in Magelang, namely BMT LE Syariah, BMT Bima, BMT Karisma,and BTM Amman. The results showed that the programs implemented by BMTin the development of MSMEs had an impact on increasing business productivityby increasing capital, increasing profits, and increasing managerial usingmusyarakah, murabahah, wakalah and qardhul hasan contracts. Also, BMThelp to market their members’ business products in cooperation with institutionsand agencies (Cooperative agencies) in the form of collaboration activities ofMSMEs empowerment.